Examining the Nexus between Education, Financial Development, Domestic Capital Formation, Openness and Renewable Energy Consumption in BRI - Qamruzzaman, Md; Monika, Monika; Kler, Rajnish (International journal of energy economics and policy, 2025)
This study investigates the impact of financial, trade, and economic openness on energy consumption, focusing on renewable, nonrenewable, and fossil energy sources in Belt and Road Initiative (BRI) nations. The BRI framework, introduced by China in 2013, emphasizes economic collaboration and infrastructure development, including renewable energy projects. As participating nations navigate energy transitions to address climate change and achieve sustainable development, understanding the role of openness is crucial. Motivated by the dual challenges of energy security and environmental sustainability, this study explores how openness influences energy consumption patterns and identifies pathways for policy intervention. Using data from 2004 to 2020, the study employs advanced econometric techniques, including Cross-Sectionally Augmented Autoregressive Distributed Lag (CS-ARDL) and Nonlinear ARDL models, to examine short- and long-term relationships. Control variables such as urbanization, financial development, and education are integrated to provide a comprehensive understanding of the dynamics. The analysis reveals that financial openness positively impacts energy consumption across all types, with a significant contribution to renewable energy in the long term. Trade openness facilitates technology transfer and renewable energy adoption, while economic openness through foreign direct investment (FDI) supports clean energy projects but also sustains fossil fuel reliance in some contexts. Urbanization drives nonrenewable energy demand but offers opportunities for renewable integration contingent on governance quality. Education enhances renewable energy consumption by fostering a skilled workforce and knowledge development. The findings suggest key policy implications. First, financial openness should be directed toward green finance and renewable energy investments. Second, trade policies must focus on reducing barriers to renewable technology imports and fostering global collaborations. Third, economic openness should prioritize sustainable FDI in clean energy sectors. Fourth, urban planning must incorporate decentralized energy systems and green technologies. Finally, investing in education and institutional reforms is essential to drive innovation and ensure effective governance. This study contributes to the discourse on energy transitions in BRI nations, emphasizing the critical role of openness and offering actionable policies to balance economic growth with sustainability.